Purification of Byproduct Sodium Chloride from Dibenzoyl Methane Process by Alkali Washing - Wang, Shan; Ni, Yuanman; Yu, Shuiqing; Li, Guangcheng; Wan, Yali; Ren, Qiyun; Huang, Xiansheng; Wei, Changting; Li, Ping; Chen, Minggong (Asian Journal of Chemistry, 2014)
DBD process produces large amounts of by-products of industrial salt. The byproduct is adhered on many kinds of organic compounds and accompanied by bad smell to pollute environment, meanwhile, the useful resource of sodium chloride is wasted. This study adopts alkaline solution to wash the by-product salt and reaches the aim of purification. It is proved the method of alkali solution washing can purify the byproduct of industrial salt effectively in this experiment. With the alkali solution washing, the organics which attached on the surface of salt react with NaOH and change into block floating in liquid at room temperature. The filtrate can be used as washing solution and recycled. The purified salt in the cleaning solution attains the national standard of industrial salt. The salt product is white and odorless. This technology of alkali solution washing to purify industrial salt not only saves the energy compared with the calcination process, but does not produce wastewater as well. By the investigation the optimum technology parameter to wash 100g raw salt is that the pH value of solution and the quality of NaOH are 7-8 and 5-6 g, respectively. The reaction time is 20 min and the residual rate of organics in the salt products is less than 0.3 %.